Screening of Amaranth (Amaranthus cruentus L.) Mutant Lines for Salinity Tolerance - ATOU, Richard; TONOUEWA, Gauthier; Wouyou, Agapit; KPOCHEME, Eustache; Missihoun, Antoine Abel; MONTCHO, David; Ahoton, Léonard E.; AGBANGLA, CLÉMENT; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD (My University, 2022)
Aims: The present study was carried out to access the salt tolerance level of nine amaranth (Amaranthus cruentus) mutant lines selected from Benin cultivar ‘Locale’ at young plants stage in comparison with the cultivar ‘Locale’ used as control. Study Design: The experiment was laid out as a Completely Randomized Design with three replications. Place and Duration of Study: The experiment was carried out in a screening house at University of Abomey-Calavi, City of Abomey-Calavi, Republic of Benin from May to June, 2020. Methodology: Three-weeks old plants of the nine stable mutant lines and the control cultivar ‘Locale’ were planted in pots containing a mixture of potting soil and sand. NaCl concentrations: 0; 100; 150 and 200 mM were given by irrigation once in two days Plant growth parameters were evaluated after two weeks. Results: Salt effect caused a reduction of young plant growth whatever the growth parameter considered with a significant disparity (p=.001) among the genotypes. Growth of the control cultivar, lines 1, 11 and 15 was most affected under salt stress whereas that of lines 18; 23 and 16 was least affected. A significant difference (p=.01 or p=.001) was observed among the salt tolerance index of genotypes. The highest salt tolerance index was observed in the line 23 followed by lines 18 and 2; and the lowest in line 15 followed by line 17, line 10 and the control cultivar. Conclusion: Some variability was observed among lines for their salt resistance. Lines 23, 18 followed by line 2 appeared as the most salt resistant types whereas line 15, followed by lines 17, 10 and the control cultivar were the most salt sensitive. Thus, lines 23, 18 and 2 are promising for salt affected areas. Further studies are necessary
Keywords: maranthus cruentus; cultivars discrimination; mutation induction; plant growth; NaCl.